Definition of the strategic directions of formation of a favorable brand of Stavropol Krai as place attractive to tourism - Ostrovskaâ Viktoriâ Nikolaevna; Voroncova Galina Vladimirovna; Momotova Oksana Nikolaevna (Ekonomski Pogledi, 2013)
In article value of branding in advance of a tourist and recreational complex of the region is proved, the directions of promotional and informational advance of a territorial tourist product are defined.